Caracterização do perfil de fluxo atômico de um conjunto de microtubos para aplicação em experimento de átomos frios - Biscassi, Mateus Antônio Fernandes (2019)
In this monograph, we will initially discuss notions about the main cooling techniques used in cold atom experiments. This will be presented in order to motivate the main theme of this work, the characterization of the velocity profile of an atomic beam. This characterization was carried out in two steps, the development of an experiment that measured the profile of the atomic beam produced in our laboratory and the development of a theoretical model to adjust the data. Through the applied method, we obtained results that agree well with the experimental data, and thus we conclude that the technique used to characterize the atomic beam was successful in describing the system.